Performance comparison of various coolants for louvered fin tube automotive radiator - Sahoo R.R.; Ghosh P.; Sarkar J. (My University, 2025)
In the present study, screening of various coolants (water, ethylene glycol, pro-pylene glycol, brines, nanofluid, and sugarcane juice) for louvered fin automotive radiator has been done based on different energetic and exergetic performance parameters. Effects on radiator size, weight and cost as well as engine efficiency and fuel consumption are discussed as well. Results show that the sugarcane juice seems to be slightly better in terms of both heat transfer and pumping power than water and nanofluid, whereas significantly better than ethylene glycol and propylene glycol. For same heat transfer capacity, the pumping power require-ment is minimum and vice-versa with sugarcane juice, followed by nanofluid, wa-ter, EG and PG. Study on brines shows an opportunity to use water+25% PG based nanofluids for improvement of performance as well as operating range. Replacement of water or brines by using sugarcane juice and water or wa-ter+25% PG based nanofluids will reduce the radiator size, weight and pumping power, which may lead to increase in compactness and overall engine efficiency or reduction in radiator cost and engine fuel consumption. In overall, both sug-arcane juice and nanofluid seem to be potential substitutes of water. However, both have some challenges such as long term stability for practical use. © 2017 Society of Thermal Engineers of Serbia.